2015
DOI: 10.1123/tsp.2013-0045
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Factors in Young Spanish Athletes: A Qualitative Focus Drawing From Self-Determination Theory and Achievement Goal Perspectives

Abstract: This study qualitatively examined how athletes perceive their coach's support for autonomy, as well as athletes' motivation, satisfaction of basic psychological needs, and the 2 × 2 achievement goal framework of young Spanish athletes. Fifteen Spanish athletes (six females and nine males) between 13 and 16 years of age were interviewed from various sporting contexts. Content analysis of the interviews revealed: the coexistence of various types of motivation for the practice of these sports by the athletes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 36 publications
1
20
0
4
Order By: Relevance
“…Athlete motivation, encompassing autonomy-supportive practice, controlling coaching or the motivational climate, has been the major focus of research to date. Typically, studies have promoted the use of autonomy-supportive practice (i.e., permitting athlete choice, empowerment and allowing learning to take place from mistakes independently), and advised against controlling forms of coaching, in order to satisfy athletes' basic psychological needs and instil more self-determined forms of motivation (Almagro, Sáenz-López, Moreno-Murcia, & Spray, 2015;Amorose & Anderson-Butcher, 2015;Hein & Jõesaar, 2015;Pope & Wilson, 2012;Reynolds & McDonough, 2015;Sheldon & Watson, 2011). These findings are consistent with Vella and Perlman's (2014) review of common approaches to coaching which presents a similar relationship between autonomy-support, basic psychological needs and intrinsic or autonomous motivation.…”
Section: Coaching Practice-athlete Outcome Relationshipsmentioning
confidence: 99%
“…Athlete motivation, encompassing autonomy-supportive practice, controlling coaching or the motivational climate, has been the major focus of research to date. Typically, studies have promoted the use of autonomy-supportive practice (i.e., permitting athlete choice, empowerment and allowing learning to take place from mistakes independently), and advised against controlling forms of coaching, in order to satisfy athletes' basic psychological needs and instil more self-determined forms of motivation (Almagro, Sáenz-López, Moreno-Murcia, & Spray, 2015;Amorose & Anderson-Butcher, 2015;Hein & Jõesaar, 2015;Pope & Wilson, 2012;Reynolds & McDonough, 2015;Sheldon & Watson, 2011). These findings are consistent with Vella and Perlman's (2014) review of common approaches to coaching which presents a similar relationship between autonomy-support, basic psychological needs and intrinsic or autonomous motivation.…”
Section: Coaching Practice-athlete Outcome Relationshipsmentioning
confidence: 99%
“…According to several authors, Self-Determination Theory (SDT) [1] and Achievement Goal Theory (AGT) [2] are the most popular and contemporary theoretical approaches used to examine motivational processes, particularly in the physical education (PE) context [3,4,5]. Looking at physiological processes, it is through PE that most children experience a wide range of motor skills.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kingston et al [3] and Almargo et al [4], results from the integration of both theories in physical activity context revealed that task orientation shows a higher correlation with autonomous regulations, and individuals’ ego oriented, although with less conclusive results, show a higher correlation with more controlled forms of motivation.…”
Section: Introductionmentioning
confidence: 99%
“…Athletes positively value when the coach builds a task-oriented motivational climate which is related to various positive consequences as enjoyment and effort. Conversely, some studies show that coaches create an ego-oriented motivational climate that is related to emphasis on winning (Almagro, Saenz-Lopez, Moreno-Murcia, & Spray, 2015) and on less autonomous motivation of athletes. In turn, the egoorientated motivation does not relate with moral values (Lee at al., 2008) as controlling coaching style does not relate with athletes' autonomous motivation and their moral behaviour (Hodge & Lonsdale, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the studies should be mentioned when athletes gain more experience in their sports, moral and competence values become more important to them, but later their significance decreases (Šukys & Jansonienė, 2012) or athletes' moral reasoning is not related to sports experience (Proios, Doganis, & Athanailidis, 2004). Commenting on the results of different studies it may be claimed that in accordance with the Self-Determination Theory athletes could experience different styles of regulation (Almagro et al, 2015).…”
Section: Discussionmentioning
confidence: 99%